Enhancing the Bioactivity of Yttria-Stabilized Tetragonal Zirconia Ceramics via Grain-Boundary Activation - Ke, Jinhuan; He, Fupo; Ye, Jiandong (ACS applied materials & interfaces, 2017)
Yttria-stabilized tetragonal zirconia (Y-TZP) has been proposed as a potential dental implant because of its good biocompatibility, excellent mechanical properties, and distinctive aesthetic effect. However, Y-TZP cannot form chemical bonds with bone tissue because of its biological inertness, which affects the reliability and long-term efficacy of Y-TZP implants. In this study, to improve the bioactivity of Y-TZP ceramics while maintaining their good mechanical performance, Y-TZP was modified by grain-boundary activation via the infiltration of a bioactive glass (BG) sol into the surface layers of Y-TZP ceramics under different negative pressures (atmospheric pressure, −0.05 kPa, and −0.1 kPa), followed by gelling and sintering. The in vitro bioactivity, mechanical properties, and cell behavior of the Y-TZP with improved bioactivity were systematically investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS), electron probe microanalysis (EPMA), and Raman spectroscopy. The results of the bioactivity test conducted by immersing Y-TZP in simulated body fluid (SBF) showed that a bonelike apatite layer was produced on the entire surface. The mechanical properties of the modified Y-TZP decreased as the negative pressure in the BG-infiltration process increased relative to those of the Y-TZP blank group. However, the samples infiltrated with the BG sol under −0.05 kPa and atmospheric pressure still retained good mechanical performance. The cell-culture results revealed that the bioactive surface modification of Y-TZP could promote cell adhesion and differentiation. The present work demonstrates that the bioactivity of Y-TZP can be enhanced by grain-boundary activation, and the bioactive Y-TZP is expected to be a potential candidate for use as a dental implant material.